2010
DOI: 10.1007/978-3-642-01539-7_4
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for the Nuclear Equation of State

Abstract: The present status of the efforts to determine the nuclear equation of state from results of heavy ion reactions and from astrophysical observations is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 120 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…In this scheme, the only input quantity we need is the bare NN interaction v in the Bethe-Goldstone equation (1). The nuclear EoS can be calculated with good accuracy in the Brueckner two hole-line approximation with the continuous choice for the single-particle potential, since the results in this scheme are quite close to the calculations which include also the three hole-line contribution [17].…”
Section: A the Brueckner-bethe-goldstone Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…In this scheme, the only input quantity we need is the bare NN interaction v in the Bethe-Goldstone equation (1). The nuclear EoS can be calculated with good accuracy in the Brueckner two hole-line approximation with the continuous choice for the single-particle potential, since the results in this scheme are quite close to the calculations which include also the three hole-line contribution [17].…”
Section: A the Brueckner-bethe-goldstone Approachmentioning
confidence: 97%
“…The experimental data on heavy ion collisions have been systematically analyzed on the basis of detailed simulations, in order to constrain not only the density dependence of the EoS, but also its isospin dependence. Excellent reviews on this subject can be found in the literature [1,2]. On the other hand, the analysis of astrophysical observational data, noticeably on compact objects, are of great relevance for the study of the nuclear EoS.…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of these constraints from HICs on compact star properties were explored by Sagert, Tolos et al (2012). For a discussion of the interplay between HICs and astrophysical data see, e.g., Aichelin and Schaffner-Bielich (2009).…”
Section: Heavy-ion Collisionsmentioning
confidence: 99%
“…Hence, kaons can escape from the high density zone unimpeded, their production rates will be controlled by the amount of compression achieved in the central region of the collision. For a recent review of the relation between the nuclear equation of state and kaon production rates in heavy-ion collisions see [29].…”
Section: Maximum Possible Mass Of Neutron Starsmentioning
confidence: 99%